Correlation between Expression of MVP, Index of p53 and AgNOR Value with Chemoradiotherapy Clinical Response of Cervical Cancer - I. Kurnia; B. Siregar; S. Soetopo; I. Ramli; T. Kurjana; D. Tetriana; B.S. Hernowo; A. Andrijono; M.D.M. Tobing (Atom Indonesia, 2014)
Cervical cancer is the most frequent cancer found in Indonesia. The primary treatment of cervical cancer at the locally advanced stage is usually performed by using radiotherapy and chemotherapy. The combination of the two techniques is often called chemoradioherapy. The response to chemoradiotherapy is influenced by biological and physical factors. Major vault protein (MVP) is a ribonucleoprotein which contributes to drug resistance in some cancers. The purposes of this research were: (1) to determine the correlation between the expression of MVP and the index of p53, including AgNOR values and index of MIB-1; and (2) between MVP and chemoradiotherapy clinical response of cervical cancer. Twenty-one microscopic slides taken from biopsy tissues of cervical cancer patients before undergoing treatment were stained to identify MVP, p53, and MIB-1 by means of immunohistochemistry techniques and AgNORs staining. After undergoing chemoradiotherapy treatment, the patients’ clinical responses were observed by pelvic control method. Experimental results showed that there was a correlation between MVP and AgNOR value (P=0.05), but no correlation between MVP and index of p53 (P=0.729), including MIB-1 LI (P=0.63), in untreated cervical cancer. In addition, there was no association between MVP and chemoradioterapy response. In conclusion, MVP expression correlates with the process of cell proliferation before the G2 phase of cell cycle in untreated cancer cells. Those have no association with clinical responses after the completion of treatment.Received: 20 November 2013; Revised: 18 July 2014; Accepted: 28 September 2014